2008
DOI: 10.1166/jnn.2008.1065
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Cationic Polydiacetylene Nanovesicles for In Vitro Gene Delivery

Abstract: Here, we report novel cationic polydiacetylene-containing nanovesicle system and its application to gene delivery in vitro. The nanovesicle was constructed using a cationic diacetylene monomer lipid (DADMDPA-bis-PCDA) which contains a quaternary ammonium head group. The cationic character of this monomer leads to the electrostatic interaction with genetic materials such as plasmid DNA forming complexes and the diacetylene groups on its hydrophobic moiety provides the further polymerization functionality upon U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…This effect has been widely examined across different pH sensitive moieties and charge groups for the purpose of optimizing gene transfection, and among them cationic polydiacetylene micelles have also proven to be an effective transfection reagent [ 19 ]. Such studies have suggested photopolymerization of cationic polydiacetylene vesicles to enhance transfection efficiency and provide some reduction in cytotoxicity, while others utilizing quaternary ammonium head groups have shown no beneficial effect of polymerization on the viability of HEK293 cells but did show an improvement in gene transfection for photopolymerized vesicles [ 20 ]. Mixtures of cationic polydiacetylene and phospholipids have also shown high rates of vesicle internalization in an example using the breast carcinoma cell line Bcap-37 [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…This effect has been widely examined across different pH sensitive moieties and charge groups for the purpose of optimizing gene transfection, and among them cationic polydiacetylene micelles have also proven to be an effective transfection reagent [ 19 ]. Such studies have suggested photopolymerization of cationic polydiacetylene vesicles to enhance transfection efficiency and provide some reduction in cytotoxicity, while others utilizing quaternary ammonium head groups have shown no beneficial effect of polymerization on the viability of HEK293 cells but did show an improvement in gene transfection for photopolymerized vesicles [ 20 ]. Mixtures of cationic polydiacetylene and phospholipids have also shown high rates of vesicle internalization in an example using the breast carcinoma cell line Bcap-37 [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Once polymerized, the vesicles could maintain their shapes for an extended time period, and decrease the vesicleevesicle and vesicleecell fusion [15]. Because of its nontoxicity, PDA vesicles have been also employed in the development of ingestible formulations [16] and gene carriers [17]. And as one of the environmentally responsive polymer materials, PDA vesicles can adopt conjugated structure distortion and color changes in response to a variety of external stimuli, such as pH [18], organic solvent [19], temperature [20], mechanical stress [21].…”
Section: Introductionmentioning
confidence: 99%
“…17 The potential application range from biosensors, 18,19 nonlinear optical devices 20 through to drug delivery. 21,22 It has been shown that diacetylene formulations 23 or polymerized liposomes 24 can deliver genes, but to the author's knowledge, few studies have been conducted on micelles.…”
Section: ' Introductionmentioning
confidence: 99%